John H. Kunkel. Society and economic growth : a behavioral perspective of social change. Nueva York : Oxford University Press, 1970. 331 p. - Reyna, José Luis (El Colegio de México A.C., 1971)
JOHN H. KUNKEL, Society and Economic Growth: A Behavioral Pers* pective of Social Change, Nueva York, Oxford University Press. 1970.